Assessing Misinformation Models, Theories, and Frameworks (MTFs): Bridging Theory and Practice in Public Health - Cildir, Zeynep (Université d'Ottawa | University of Ottawa, 2025)
Since the COVID-19 pandemic, there has been a surge of health misinformation, prompting two key outcomes: a significant increase in misinformation research, with many models, theories and frameworks (MTFs) seeking to describe, explain, and propose strategies against misinformation, and development of real-world interventions by public health organizations. However, the extent to which these MTFs inform real-world efforts remains unclear. This thesis aims to 1) assess the quality and nature of existing misinformation MTFs, and 2) explore the integration of such MTFs within the intervention development processes. Objective 1 is addressed through a scoping review, appraising misinformation MTFs through the purpose, characteristics, usability, implementability and testability. Objective 2 involves semi-structured interviews capturing the development process of misinformation countering initiatives. These findings can guide developers in selecting relevant misinformation MTFs and highlight how theoretical insights could translate into real-world misinformation countermeasures.
Keywords: misinformation; framework; quality; implementation science; theories; models; sickle cell disease